The Effect of Service Quality, User-Friendliness, and Trust on Customers' Interest In Using BNI Mobile Banking - Nail Hani; Andyan Utama (Penerbit Jurnal Indonesia, 2025)
The rapid development of digital technology has significantly influenced the banking industry, particularly in the adoption of mobile banking services. This study aims to analyze the effect of service quality, ease of use, and trust on customer interest in using BNI mobile banking. A quantitative approach was applied with a descriptive research design, involving 100 respondents who are customers of BNI Meruya Branch. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 25. The findings show that ease of use and trust have a positive and significant effect on customer interest in using BNI mobile banking, while service quality, although positive, does not significantly influence customer interest. These results indicate that the practicality of the application and the assurance of security are more decisive factors in influencing customer decisions compared to general service quality. This research contributes to the literature on digital banking adoption and provides practical implications for banking institutions to strengthen customer trust and simplify mobile banking features. Future studies are recommended to expand the research scope with larger samples and integrate additional variables such as perceived risk, bank reputation, and innovation to obtain more comprehensive insights.